Simulasi Operasi Waduk Lamong untuk Kepentingan Air Baku dan Irigasi - Sulistiono, Andi; Rahmandani, Dadan; Triyono, Joko (Balai Teknik Irigasi, 2014)
Lamong River Basin is located in the Lamongan and Mojokerto Regency for the upstream part, Gresik Regency and Surabaya City for the downstream part. Lamong River Basin has area about Â± 720 km2 with the main river channel has length about Â± 103 km. Hydrological condition of Lamong River Basin is critical, as a result, most part of the Lamong River Basin that located in the region of Gresik and Surabaya Regency, every year is suffering from flooding due to overflowing. By contrast, in the upstream of Lamong River Basin is always shortage of water in the dry season. In the study, inflow discharge of Lamong Reservoir are obtained by synthetic streamflow data generation using Thomas Fiering method. Historical flow data are obtained by transforming rain data into discharge data using Mock model and using rainfall data of Ngimbang Station, Bluluk Station and Mantup Station and also discharge measurement data of Boboh Station in 1995-1997. The calculation of raw water demand is based on a standard requirement of raw water from Directorate General Human Settlements, Ministry of Public Works in 2003, while the irrigation water requirement is calculated by Standard Irrigation Planning (KP-01) in 1986. Simulations are conducted from the year of 2016 to 2025 with the use of Standard Operating Rule (SOR).The results show that the needs of raw water by people served by the Lamong Reservoir is equal to 5,70 million m3 in 2015 and 5,74 million m3 in 2025. Reliability of Lamong Reservoir in serving the needs of raw water will be achieved 99,17 % by the planting area covering 2.117 Ha with irrigation water reliability in serving 96,25 %.